2015
DOI: 10.5472/mmjcr.2802.11
|View full text |Cite
|
Sign up to set email alerts
|

The olfactory reference syndrome treated with escitalopram: A case report

Abstract: Olfactory reference syndrome (ORS) is a clinical condition that causes patients to be excessively anxious about emitting body odors that may be offensive for other people. This causes heavy distress and depression, even leading to suicides. The ORS is classifised under different categories.In this paper, we report a patient with ORS. She has a preoccupation of foul body odor emanating from her anal region which we treated with escitalopram. We also discuss, within the framework of this case, the place of ORS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…There are no randomised controlled trials on the use of psychotropics in ORD. There have been reports of specialists using antidepressants of various classes [30][31][32][33], both typical and atypical antipsychotics [34][35][36][37][38][39][40][41], as well as combinations of antipsychotics and antidepressants [42][43][44]. Various degrees of success have been reported with individual and combination therapy.…”
Section: Treatmentmentioning
confidence: 99%
“…There are no randomised controlled trials on the use of psychotropics in ORD. There have been reports of specialists using antidepressants of various classes [30][31][32][33], both typical and atypical antipsychotics [34][35][36][37][38][39][40][41], as well as combinations of antipsychotics and antidepressants [42][43][44]. Various degrees of success have been reported with individual and combination therapy.…”
Section: Treatmentmentioning
confidence: 99%
“…Unfortunately, literature on ORS is very sparse and research is limited. Available reports are mainly limited to case reports, case series, or literature reviews; as of yet, there are no diagnostic criteria clearly agreed upon that define the syndrome [ 9 , 10 ]. Few systematic studies have outlined clinical symptoms of ORS, other than the Pryse-Phillips paper; an Internet based study by Greenberg and colleagues describes the complexity of the clinical features; they reported that nearly all participants performed rituals in response to ORS beliefs and endorsed avoidance of usual social and occupational activities including significant avoidance of intimacy, physical activities, and various social situations [ 1 , 10 ].…”
Section: Introductionmentioning
confidence: 99%